Good teaching—The adaptive balance between compulsion and freedom - Kiel, Ewald; Weiss, Sabine (Frontiers in Education, 2022)
What is good teaching? This question is as old as people have reflected on this topic, and its answers in the European context date back to antiquity. This essay elaborates on and justifies one complex answer to the question: good teaching is the adaptive balance between compulsion and freedom. The key questions addressed by the essay are as follows: (1) What arguments favor teaching within a framework of compulsion and what arguments favor teaching in a framework of freedom? (2) How can these possibilities be reconciled? (3) Does a myth of good teaching derive from these possibilities? To answer these questions, we first examine the different dimensions related to good teaching in science and other domains of life. We then develop criteria for defining compulsion and freedom in the context of teaching. This is followed by depicting arguments for organizing teaching in a framework of compulsion and those for organizing teaching in a framework of freedom. The thesis (compulsion) and antithesis (freedom) are then synthesized by constructing a concept of a balance between both positions according to the ideas of philosophy, sociology, theories of education, and learning theory. Therefore, the basic approach of this essay is dialectical. We select big ideas, confront them against each other, and attempt to find a synthesis without any claim to the historical completeness or completeness of concepts. Based on history, we emphasize the idea that, from the time of enlightment to modern learning theories, similar lines of arguments support each other.